Monitoring of Athalassa’s Lake: Fish kills event, cyano-HABs bloom and treatment with hydrogen peroxide and hydrogen peroxide releasing granules - Keliri, Eleni; Antoniou, Maria G. (My University, 2022)
Surface water monitoring is essential for maintaining a healthy status and protect the biodiversity of aquatic biotopes. Unfortunate events of high nutrient load, organic matter input, and swage run-offs that lead to the formation of cyano-HABs are mostly unpredictable and thus highly efficient methods are required to be applied for the in-situ restoration. During the monitoring (2020-2021), a massive fish kills event was occurred, which followed by a blooming period, that raised many questions regarding the source of toxicity in the lake. Water samples were analyzed for cyanobacteria and toxin producing genes presence, as well as for their physicochemical water characteristics (nutrients, COD, pH, conductivity, dissolved solids, instantaneous fluorescence and quantum yield). In order to find effective, cost efficient, and environmentally friendly mitigation techniques, water was collected during the blooming periods and utilized in treatment experiments with liquid hydrogen peroxide, (single and multiple H2O2 doses), and calcium peroxide granules (CaO2). Multiple doses of liquid H2O2 proved to be more efficient and had long-lasting effects in contrast with the single dose of liquid H2O2, which was consumed rapidly after the addition. CaO2 granules were efficient to treat the bloom by gradually releasing into the water H2O2, simulating multiple additions of H2O2.